1-tanx/1+tanx=1-sin2x/cos2x
2 answers
see the related questions below.
(1-tanx)^2/(1-tan^2 x)
= (1-2tanx+tan^2 x)/(1-tan^2 x)
= (1+tan^2 x)/(1-tan^2 x) - 2tanx/(1-tan^2 x)
= sec^2x/(1-tan^2 x) - tan2x
= 1/(cos^2x-sin^2x) - tan2x
= 1/cos2x - sin2x/cos2x
= (1-sin2x)/cos2x
steve can i ask u what happen to the 1-tan^2x in the expression sec^2x/(1-tan^2 x) - tan2x its gone in the next line.
= (1-2tanx+tan^2 x)/(1-tan^2 x)
= (1+tan^2 x)/(1-tan^2 x) - 2tanx/(1-tan^2 x)
= sec^2x/(1-tan^2 x) - tan2x
= 1/(cos^2x-sin^2x) - tan2x
= 1/cos2x - sin2x/cos2x
= (1-sin2x)/cos2x
steve can i ask u what happen to the 1-tan^2x in the expression sec^2x/(1-tan^2 x) - tan2x its gone in the next line.